POSSIBILITIES OF USING ACETATE THREADS IN THE TEXTILE INDUSTRY - Tadjibayev , Anvar Avazovich (Educational Research in Universal Sciences, 2024)
This study explores the possibilities of using acetate threads in the textile industry. Acetate, a synthetic fiber derived from cellulose, has unique properties that make it suitable for various textile applications. The research investigates the potential benefits and challenges of incorporating acetate threads into different textile products, such as clothing, upholstery, and technical textiles. Additionally, the study examines the environmental impact and sustainability aspects associated with acetate thread production and usage in the textile industry.